Obituary: Late Prof. Dr. Neelam Adhikari (Journal of Patan Academy of Health Sciences, 2020)
With heavy heart we mourn the demise of Prof. Dr. Neelam Adhikari, who passed away on November 01, 2020, after a short battle with cancer.